EU-Asia free trade areas? Economic and policy considerations - Michael G. Plummer (Asian Development Bank Institute (ADBI), 2010)
In this paper, we analyzed key aspects of the changing economic relationship between the European Union (EU) and Asia, and explored the potential economic ramifications of deeper EU-Asian economic cooperation. We also investigated the possible costs to the EU of remaining disengaged from the Asian integration process and the likely impact of multi-nested EU-Asian trade agreements. Our empirical review of CGE models revealed trivial effects of several possible EU-Asian accords (e.g., EU-India, EU-ASEAN, EU-Republic of Korea). In part, this is a result of relatively small trade shares, open markets, and restrictions in the models, particularly in that they excluded behind-the-border effects. We also presented two CGE models that estimated the potential negative effects of Asian/Asia-Pacific regional accords on the EU, and likewise found small effects. Nevertheless, using a highly-disaggregated (partial-equilibrium) approach, we argued that high-quality FTAs in Asia could be quite detrimental to the EU, particularly in key sectors. The push toward a Free Trade Area of the Asia Pacific could be particularly worrisome to the EU. We therefore concluded that it makes sense for the EU to be more aggressive in pursuing prospective trade agreements with Asia.
Keywords: F13; F15; 330; Freihandelszone; Handelsregionalismus; Außenhandelseffekt; Allgemeines Gleichgewicht; EU-Staaten; Asien